Analysis About Inflation Persistence in West Sumatra Province: Pre-Post the COVID-19 Pandemic - Safela, Remon Astra; Satrianto, Alpon (Journal of Ecohumanism, 2025)
This research is based on significant inflation fluctuations due to global economic disruptions, changes in consumption patterns, and the impact of a pandemic that triggers shock inflation away from its average value. The purpose of the study is to analyze between inflation persistence before and after the COVID-19 pandemic in West Sumatra Province. The variables used in this study include general inflation and commodity group inflation. This study uses a univariate autoregressive (AR) approach with monthly inflation time series data for 2017-2019 (pre-pandemic) and 2021-2023 (post-pandemic). Data obtained from the Central Bureau of Statistics of West Sumatra. The results showed that the persistence rate of general inflation before and after the pandemic was in a controlled category with an average length of time back to its natural level of less than one month. All commodity group inflation variables such as processed food, housing, health, and education are in the low inflation persistence category with the length of time to return to its natural level of less than 3 months both before and after the pandemic. The results are different for the inflation variables of the transportation, communication, and financial services commodity groups which have a low inflation persistence rate before the pandemic, but high after the COVID-19 pandemic with a length of time to return to its natural level of 8.09 months. This research is expected to help policy makers in formulating strategic steps to maintain inflation and regional economic stability.